59.0k views
19 votes
Find the solution to the equation:
f(x)=x^2-4x+3
Please show work!

2 Answers

4 votes

Let's see


\\ \rm\rightarrowtail f(x)=0


\\ \rm\rightarrowtail x^2-4x+3=0


\\ \rm\rightarrowtail x^2-3x-x+3=0


\\ \rm\rightarrowtail x(x-3)-1(x-3)=0


\\ \rm\rightarrowtail (x-1)(x-3)=0


\\ \rm\rightarrowtail x=1,3

User Sheo Sagar
by
5.5k points
4 votes

Answer:

  • two solutions

x = 1, 3

Step-by-step explanation:


\sf f(x)=x^2-4x+3


\rightarrow \sf x^2-4x+3=0


\rightarrow \sf x^2-3x-x+3=0


\rightarrow \sf x(x-3)-1(x-3)=0


\rightarrow \sf (x-1)(x-3)=0


\rightarrow \sf x-1=0, \ x-3=0


\rightarrow \sf x=1, \ x=3

Thus, there are two solutions and the values are 1 and 3

User Bharat Gulati
by
4.8k points